EFFORTS TO IMPROVE STUDENTS COMMUNICATION SKILLS THROUGH THE APLICATION OF THE TEAM QUIZ LEARNING METHOD - Fulkanis Fulkanis (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This research is motivated the low learning activity carried out by students which still passive so that the lack of student skills, one of which is communication skills. As an effort to improve students communication skills is the aplication of a team quiz. Team quiz can be interpreted as a learning activity carried out in groups to discuss a material that is being studied. This research was conducted in class V SDN 016 Sako, Pangean District, totaling 75 students. The instrument used was the observation of students' communication skills. The results showed that the skills of students in the first cycle were 71.44 which was a good category, in the second cycle it increased to 83.23 in the very good category. Based on the research results, it can be concluded that the application of the team quiz method can improve students' communication skills. Students are able to ask questions and explain answers fluently and use language that is easy to understandably.